Correlation between the heating value and the chemical characteristics of Eucalyptus biomass - Bonfatti Junior, Eraldo Antonio [UNESP]; Oliveira, Rudson Silva; Lengowski, Elaine Cristina; Andrade, Alan Sulato de; Silva, Dimas Agostinho da (Univ Federal Santa Maria, 2025)
The chemical characteristics of lignocellulosic biomass determine its suitability as an energy source, affecting its combustibility, flame stability, and overall energy efficiency. Therefore, this study assessed the correlation between the chemical characteristics and higher heating value (HHV) in Eucalyptus biomass components (wood, bark, branches, and leaves) of three species (E. benthamii, E. dunnii, and E. saligna). The results revealed varying chemical compositions among the components and species, which impacted the HHV differently. Notably, volatile materials positively influenced the HHV, whereas excessive ash content negatively affected the energy potential. Positive correlations with HHV were observed for the total extractives content in the bark, total lignin content in the leaves, volatile materials content in the bark, leaves, and stem, and fixed carbon content in the stem. Conversely, the holocellulose content reduced the bark HHV. Volatile materials, except in the branches, efficiently increased the HHV. None of the chemical characteristics had a significant impact on the branches HHV.
Correlação entre o poder calorífico e as características químicas da biomassa de Eucalyptus
Keywords: wood; bioenergy; biofuel; Pearson correlation